The Effect of Eye Movement Desensitization and Reprocessing (EMDR) Therapy on Reducing Craving in Populations with Substance Use Disorder: A Meta-Analysis - Diana Emilia Martínez-Fernández; David Fernández-Quezada; Andrea P. Garzón-Partida; Irene G. Aguilar-García; Joaquín García-Estrada; Sonia Luquin (Brain Sciences, 2024)
Substance use disorder (SUD) significantly impacts public health, economics, and legal systems worldwide. Eye Movement Desensitization and Reprocessing (EMDR) was initially developed in the late 1980s as a therapeutic approach for post-traumatic stress disorder (PTSD), using bilateral stimulation to integrate traumatic memories with calming physiological responses. However, the effectiveness of EMDR in treating SUD remains unclear. This study aims to conduct a systematic review and meta-analysis of the impact of EMDR therapy on craving reduction in individuals with SUD. The search was conducted using databases such as PubMed and Web of Science, focusing on studies that measured craving and employed EMDR interventions. Both random and fixed effects models were used to pool effect sizes, utilizing an R software meta-package (R-4.4.1). The study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The results indicated a significant reduction in cravings among patients undergoing EMDR therapy. Specifically, under the fixed effect model, the standardized mean difference (SMD) was −0.866 with a 95% confidence interval ranging from −1.121 to −0.611 (z = −6.66, p < 0.0001). These findings may demonstrate the significant efficacy of EMDR therapy in decreasing cravings in people with SUD.